2018
DOI: 10.1016/j.jcis.2017.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Light-sensitive dextran-covered PNBA nanoparticles as triggered drug delivery systems: Formulation, characteristics and cytotoxicity

Abstract: Whatever the process, the photosensitive property and the colloidal stability of NPs in the presence of salts were proved. However, triazole rings between the dextran shell and the PNBA core avoid the dextran shell desorption in the presence of SDS. NPs' biocompatibility towards Caco-2 was proved and 100% cell viability was still observed after exposure to NPs following by 60 s UV-irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 56 publications
(89 reference statements)
1
25
0
Order By: Relevance
“…Similarly, CuAAC is a general method for the synthesis of click-crosslinked nanoparticles; that is, viral nanoparticles crosslinked with "clickable" fluorescent crosslinkers at the interface, [49] drug nanocrystals with PEG nanocages as nonsheddable stabilizers, [50] drug-conjugated biodegradable nanoparticles by click-crosslinking in miniemulsion, [51] sizerestricted robust and functionalizable hydrophilic nanocrystals, [52] degradable polymeric nanoparticles built from thermoresponsive polymers, [53] and light-sensitive dextrancovered nanoparticles. [54] For example, Cheng et al present a type of biodegradable drug-polymer nanoconjugates via CuAAC. [51] Diazide-functionalized paclitaxel that served as both the drug and crosslinker was synthesized as shown in Figure 4a.…”
Section: Click-crosslinked Nanoparticlesmentioning
confidence: 99%
“…Similarly, CuAAC is a general method for the synthesis of click-crosslinked nanoparticles; that is, viral nanoparticles crosslinked with "clickable" fluorescent crosslinkers at the interface, [49] drug nanocrystals with PEG nanocages as nonsheddable stabilizers, [50] drug-conjugated biodegradable nanoparticles by click-crosslinking in miniemulsion, [51] sizerestricted robust and functionalizable hydrophilic nanocrystals, [52] degradable polymeric nanoparticles built from thermoresponsive polymers, [53] and light-sensitive dextrancovered nanoparticles. [54] For example, Cheng et al present a type of biodegradable drug-polymer nanoconjugates via CuAAC. [51] Diazide-functionalized paclitaxel that served as both the drug and crosslinker was synthesized as shown in Figure 4a.…”
Section: Click-crosslinked Nanoparticlesmentioning
confidence: 99%
“…[36,37] Recent developments in this area have applied the principle of targeting lectins with glycopolymers in more refined systems, using sequenced defined polymers alone and in combination with stimuli responsive polymers to elicit a more specific biological targeting. [37][38][39][40][41] Among the many stimuli responsive systems reported, poly(N-isopropylacrylamide) is commonly used for temperature response, where heating above the cloud point of the system triggers a self-assembly or reveals a glycopolymer. [42,43] Next to temperature, pH is arguably one of the most ubiquitously exploited stimuli, used to induce polymer assembly and disassembly, or to release a covalently bound drug molecule via an acid cleavable linker; these among many other unique systems represent a growing and active field of research in drug delivery.…”
Section: Doi: 101002/marc201800122mentioning
confidence: 99%
“…In particular, specific sugar moieties can be positioned at the surface of the particles, to target a class of protein receptors known as lectins. Previous research into using sugar‐lectin targeting for drug delivery has shown that presenting the targeting sugar in a high concentration, such as that on the surface of a particle, increases the targeting efficiency of a drug delivery vector, taking advantage of the “glycocluster effect.” Recent developments in this area have applied the principle of targeting lectins with glycopolymers in more refined systems, using sequenced defined polymers alone and in combination with stimuli responsive polymers to elicit a more specific biological targeting . Among the many stimuli responsive systems reported, poly( N ‐isopropylacrylamide) is commonly used for temperature response, where heating above the cloud point of the system triggers a self‐assembly or reveals a glycopolymer .…”
Section: Introductionmentioning
confidence: 99%
“…The reaction efficiency was evaluated thermogravimetrically by determining the solid content of the obtained dispersion. Chemical analyses of the insoluble products were performed using attenuated total reectance Fourier transform infrared spectroscopy (ATR-FTIR) and high resolution solid- state 13 C nuclear magnetic resonance (NMR). 50,51 The characteristics of the synthesized nanocapsules, i.e.…”
Section: Synthesis Of Nanocarriersmentioning
confidence: 99%
“…Stimuli-responsive nanocarriers that respond to dened triggers (such as pH, temperature, enzymes, light and redox species) have gained enormous interest because they aid in "release on demand". 1,11,13 Since variations in pH exist within different physiological environmentsdifferent organs, tissues, and cellular compartments possess mostly different pH values, as well as differences between normal and abnormal (cancer, inammation) pathological conditionsdeveloping nanocarriers that respond to the pH of the local environment is highly attractive. [14][15][16] For this purpose, pH-responsive nanocarriers exploiting a release prole stimulated by the intracellular acidic environment (pH $ 5.5-6.0 and pH $ 4.5-5.0 in endosomes and lysosomes, respectively) and suppressed in the systematic circulation at physiological pH of 7.4 are of special interest.…”
Section: Introductionmentioning
confidence: 99%